2021
DOI: 10.3390/nu13020465
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Importance of Selected Fresh Fishes, Shrimps and Mollusks to Meet Compliance with Nutritional Guidelines of n-3 LC-PUFA Intake in Spain

Abstract: Fishery products are the main source of dietary n-3 long-chain polyunsaturated fatty acids (n-3 LC-PUFA). Following the European Commission’s request to address the risks and benefits of seafood consumption, and taking into account the great variability of nutrient and contaminant levels in fishery products, the present work aims to estimate the n-3 LC-PUFA provided per serving of selected fishes, shrimps and mollusks that are commonly consumed in Spain. This would enable the establishment of a risk–benefit an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 45 publications
4
17
0
Order By: Relevance
“…In fact, there are guidelines that recommend consuming fish at least twice a week, thereby introducing about 250 mg/day of EPA + DHA [4,8]. From studies conducted by the EFSA Panel on Nutrition, Novel Foods and Food Allergens (NDA EFSA Panel), it has been observed that consumption of 1-2 servings of seafood products per week, and up to 3-4 servings per week in the case of pregnant women, results in functional benefits related to neurodevelopment in children and lower risk of mortality from coronary heart disease in adults [9].…”
Section: Of 12mentioning
confidence: 99%
“…In fact, there are guidelines that recommend consuming fish at least twice a week, thereby introducing about 250 mg/day of EPA + DHA [4,8]. From studies conducted by the EFSA Panel on Nutrition, Novel Foods and Food Allergens (NDA EFSA Panel), it has been observed that consumption of 1-2 servings of seafood products per week, and up to 3-4 servings per week in the case of pregnant women, results in functional benefits related to neurodevelopment in children and lower risk of mortality from coronary heart disease in adults [9].…”
Section: Of 12mentioning
confidence: 99%
“…The numerous nutritional benefits of fish consumption have been associated with the high content of proteins of high biological value, an adequate contribution of polyunsaturated fatty acids (omega-3) and low cholesterol levels and its rich content of vitamins (mainly A and D) and minerals [5][6][7][8]. In this section we will highlight the nutritional composition and bioactive compounds of oily fish, paying special attention to the species P. glauca, I. oxyrinchus, X. gladius and T. thynnus.…”
Section: Composition Of Nutritional and Bioactive Compounds In Select...mentioning
confidence: 99%
“…Among PFA, eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) are the most abundant. These compounds are well-known for having beneficial effects on health, including anti-inflammatory properties and neurological and cardiovascular protection [2,8,22,23]. Other important data include the proportion of omega-3 and omega-6 fatty acids.…”
Section: Lipids and Fatty Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regular intake of sufficiently high quantities of polyunsaturated fatty acids (PUFAs) has been needed to reduce the incidences of innumerable types of ailments and chronic diseases, including psoriasis, bowel diseases, mental illnesses, cancer, rheumatoid arthritis, cardiovascular diseases, diabetes, pulmonary disorders, coordination disorders, movement illnesses, obesity, and weak bones [ 1 , 2 , 3 , 4 ]. As a result, the consumption of foods rich in PUFAs is strongly encouraged by health agencies around the globe.…”
Section: Introductionmentioning
confidence: 99%